Electrospun porous polylactic acid fibers containing CdS for degradation of methylene blue - Ho, Chit Seng; Zainal Abidin, Nur Hafizah; Nugraha, Muhammad Wahyu; Sambudi, Nonni Soraya; Ali, Fathilah; Wirzal, Mohd Dzul Hakim; Kasmiarno, Laksmi Dewi; Adli, Sarah Amalina (Korean Fiber Society, 2020)
The immobilization of photocatalyst in polymer fibers has been found to improve photodegradation of dye and recyclability of material. In this study, porous polylactic acid (PLA) fibers were utilized as photocatalyst support using electrospinning technique to synthesis the fibers. The cadmium sulfide (CdS) was embedded in fibers at the amount of 1 wt%, 3 wt%, and 5 wt% as photocatalyst agent with absorption in visible light range. The electrospun fibers experienced increasing in diameter for 2.6 times (from 175 nm to 450 nm), due to incorporation of CdS. The synthesized CdS has bandgap of 2.35 eV, and its presence in composite fibers can be detected by using energy dispersive X-ray (EDX) and X-ray diffraction (XRD) analyses. The photodegradation was performed under low-powered halogen lamp, with 90 % removal of methylene blue (MB) after 10 hours of irradiation using CdS(3 wt%)/PLA fibers. This result shows higher performance in comparison with PLA and CdS which could only remove 57 % and 65 % of MB, respectively. The recyclability of composite was tested with satisfying performance; with around 60 % of MB removal was maintained after five times of recycle experiments.